2003
DOI: 10.1242/jeb.00262
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater environment affects growth rate and muscle fibre recruitment in seawater stages of Atlantic salmon (Salmo salarL.)

Abstract: The influence of freshwater environment on muscle growth in seawater was investigated in an inbred population of farmed Atlantic salmon (Salmo salar L.). The offspring from a minimum of 64 families per group were incubated at either ambient temperature (ambient treatment) or in heated water (heated treatment). Growth was investigated using a mixed-effect statistical model with repeated measures, which included terms for treatment effect and random fish effects for individual growth rate (α) and the instantaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 66 publications
6
90
0
Order By: Relevance
“…In contrast, the 16L:8D group did not reach the size of the other groups. In salmon, the body weight was also higher in the 24L group than in the natural photoperiod group four months and two weeks after transferring the salmons to natural photoperiod (Johnston et al, 2003b(Johnston et al, , 2004. In two groups of cod reared at 24L and at a natural photoperiod for 120 days, Nagasawa et al (2012) observed that the muscle growth of the 24L group was greater not only at 120 days, but also two months after the two groups were transferred to a natural photoperiod (at 180 days).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, the 16L:8D group did not reach the size of the other groups. In salmon, the body weight was also higher in the 24L group than in the natural photoperiod group four months and two weeks after transferring the salmons to natural photoperiod (Johnston et al, 2003b(Johnston et al, , 2004. In two groups of cod reared at 24L and at a natural photoperiod for 120 days, Nagasawa et al (2012) observed that the muscle growth of the 24L group was greater not only at 120 days, but also two months after the two groups were transferred to a natural photoperiod (at 180 days).…”
Section: Discussionmentioning
confidence: 95%
“…Jhonston et al [32] and Zimmerman & Lowery [33] state that muscular development by hyperplasia is replaced by hypertrophy of the muscular cells when a fish reaches 44% of its final size; however, this can vary with species. Furthermore, Rowlerson and Veggetti [30] reported that fish have an undetermined growth, which makes it difficult to establish the final weight of an adult.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we tested the null hypothesis that muscle cellularity was the same in all morphs of Arctic charr in Thingvallavatn, reflecting their recent diversification. The number of muscle fibres formed at each phase of myogenesis is sensitive to egg incubation temperature (Stickland et al, 1988;Johnston et al, 2000aJohnston et al, ,b, 2003cJohnston and Hall, 2004). Variation in spawning time and the influence of cold groundwater on spawning sites give rise to the possibility of differences in development temperature between morphs (Skúlason et al, 1989a).…”
Section: Growth In Arctic Charrmentioning
confidence: 99%
“…The environmental temperature during early development has been shown to affect the number of muscle fibres produced at each stage of myogenesis in salmonids (Stickland et al, 1988;Johnston et al, 2000bJohnston et al, , 2003c) and other teleosts (Ayala et al, 2000;Johnston et al, 1998). Temperature regimes that result in a higher fibre number have been associated with a higher density of myogenic progenitor cells (Johnston et al, 2000a(Johnston et al, , 2003c.…”
Section: The Origins Of Different Patterns Of Fibre Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation